Oxytocin: An Old Hormone, a Novel Psychotropic Drug and its Possible Use in Treating Psychiatric Disorders - Marazziti, Donatella; Diep, Phuoc-Tan; Carter, Sue; Carbone, Manuel G. (Current Medicinal Chemistry, 2022)
Background: Oxytocin is a nonapeptide synthesized in the paraventricular and supraoptic nuclei of the hypothalamus. Historically, this molecule has been involved as a key factor in the formation of infant attachment, maternal behavior and pair bonding and, more generally, in linking social signals with cognition, behaviors and reward. In the last decades, the whole oxytocin system has gained a growing interest as it was proposed to be implicated in etiopathogenesis of several neurodevelopmental and neuropsychiatric disorders. Methods: With the main goal of an in-depth understanding of the oxytocin role in the regulation of different functions and complex behaviors as well as its intriguing implications in different neuropsychiatric disorders, we performed a critical review of the current state of the art. We carried out this work through the PubMed database up to June 2021 with the search terms: 1) “oxytocin and neuropsychiatric disorders”; 2) “oxytocin and neurodevelopmental disorders”; 3) “oxytocin and anorexia”; 4) “oxytocin and eating disorders”; 5) “oxytocin and obsessive- compulsive disorder”; 6) “oxytocin and schizophrenia”; 7) “oxytocin and depression”; 8) “oxytocin and bipolar disorder”; 9) “oxytocin and psychosis”; 10) “oxytocin and anxiety”; 11) “oxytocin and personality disorder”; 12) “oxytocin and PTSD”. Results: Biological, genetic, and epigenetic studies highlighted quality and quantity modifications in the expression of oxytocin peptide or in oxytocin receptor isoforms. These alterations would seem to be correlated with a higher risk of presenting several neuropsychiatric disorders belonging to different psychopathological spectra. Collaterally, the exogenous oxytocin administration has shown to ameliorate many neuropsychiatric clinical conditions. Conclusion: Finally, we briefly analyzed the potential pharmacological use of oxytocin in a patient with severe symptomatic SARS-CoV-2 infection due to its anti-inflammatory, antioxidative and immunoregulatory properties.
Keywords: oxytocin receptor